In patients with type 2 diabetes chronic kidney disease is a modifiable cardiovascular risk factor. (3rd October 2022) - Agarwal, R; Pitt, B; Rossing, P; Anker, S D; Filippatos, G; Ruilope, L M; Kovesdy, C P; Tuttle, K; Vaduganathan, M; Wanner, C; Bansilal, S; Gebel, M; et al.
Abstract: Background/Introduction: Chronic kidney disease (CKD) in patients with type 2 diabetes (T2D) is associated with an increased risk of cardiovascular (CV) events. The modifiability of CKD-associated CV risk in patients with T2D across a spectrum of CKD stages remains unknown. Purpose: To test whether CKD, as defined jointly by estimated glomerular filtration rate (eGFR) and albuminuria (urine albumin-to-creatinine ratio [UACR]), is a modifiable CV risk factor in patients with T2D. Furthermore, to estimate the population-wide reduction in first CV events in the US if all eligible patients were treated with finerenone. Methods: We estimated the incidence rates of CV events (composite of CV death, non-fatal stroke, non-fatal myocardial infarction, or hospitalisation for heart failure) over a median follow-up of 3.0 years in 13, 026 patients with CKD and T2D, treated with finerenone or placebo, in a joint analysis by eGFR and UACR categories. Patients were from FIDELITY, a prespecified pooled analysis of two phase III trials, and had an eGFR ≥25 ml/min/1.73 m 2 and UACR 30–5000 mg/g at screening.The potential impact of finerenone treatment on the US population was evaluated by simulating the number of first CV events that could be prevented per year with finerenone, using incidence rates from FIDELITY and prevalence rates of CKD in patients with T2D from the National Health and Nutrition Examination Survey (NHANES). Results: Lower eGFR and higher UACR categories were associated with higher incidences of CV events in finerenone and placebo recipients (Figure). Finerenone reduced CV risk versus placebo (hazard ratio 0.86; 95% CI 0.78–0.95; p=0.0018) without evidence of moderation of risk reduction by combined eGFR and UACR categories (p interaction = 0.66; Figure 1). Using NHANES, a total of 6.4 million treatment-eligible individuals with CKD and T2D were identified; 75% had CKD with an eGFR ≥60 ml/min/1.73 m 2 and 25% had CKD with an eGFR <60 ml/min/1.73 m 2 . Simulations using this NHANES population projected that 1 year of finerenone treatment could prevent 38, 359 CV events in US patients with CKD and T2D, with 66% of events prevented in patients with eGFR ≥60 ml/min/1.73 m 2 . Conclusions: Higher albuminuria and lower eGFR are associated with increased CV risk in patients with T2D. Across a range of eGFR and albuminuria categories, CV risk is modifiable. Therefore, CKD is a modifiable CV risk factor in part mediated by mineralocorticoid receptor overactivation. UACR screening to identify patients with T2D and albuminuria with an eGFR ≥60 ml/min/1.73 m 2 is likely to provide a significant opportunity for population benefits. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Bayer AG